2018
DOI: 10.1186/s41610-018-0079-y
|View full text |Cite
|
Sign up to set email alerts
|

Control of runner reed (Phragmites japonicus) in lentic wetlands

Abstract: In lotic wetlands, runner reed (Phragmites japonicus) plays a role as a pioneer, which helps other plant species to settle by making dense roots trapping floating-sediments. In lentic wetlands, on the other hand, P. japonicus could play a role as an invader threatening biodiversity by forming tall and dense stands. To conserve an abandoned paddy terrace in mountainous areas, a habitat of an endangered dragonfly species (Nannophya pygmaea), from the monotypicoccupation by P. japonicus, we applied three kinds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hydrological regimes including water depth (level), amplitude, and period are influential factors in determining the characteristics of wetland ecosystems (Carter 1986;Aldous et al 2005). In particular, water depth as a physical characteristic is known as a critical driver determining the vegetational components of wetland ecosystems (Nam et al 2014;Byun et al 2017;Hong et al 2018). On the other hand, decreases in water depth may alter the vegetational characteristics of wetland ecosystems and even cause terrestrialization (Lee et al 2002;Byun et al 2008), which means the transformation of wetlands into upland-like fields (Kirschner et al 2001).…”
Section: Effects Of Drawdown On Vegetation and Flora Of Aptsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hydrological regimes including water depth (level), amplitude, and period are influential factors in determining the characteristics of wetland ecosystems (Carter 1986;Aldous et al 2005). In particular, water depth as a physical characteristic is known as a critical driver determining the vegetational components of wetland ecosystems (Nam et al 2014;Byun et al 2017;Hong et al 2018). On the other hand, decreases in water depth may alter the vegetational characteristics of wetland ecosystems and even cause terrestrialization (Lee et al 2002;Byun et al 2008), which means the transformation of wetlands into upland-like fields (Kirschner et al 2001).…”
Section: Effects Of Drawdown On Vegetation and Flora Of Aptsmentioning
confidence: 99%
“…On the other hand, it has also been reported that the introduction of tree species such as Salix spp. could be prevented in APTs when deep water condition is maintained (Hong and Kim 2013c;Choi and Kim 2015;Hong et al 2018).…”
Section: Effects Of Drawdown On Vegetation and Flora Of Aptsmentioning
confidence: 99%
See 2 more Smart Citations